CONTEMPORARY ASPECTS OF THE TREATMENT OF ODONTOGENIC JAW CYSTS IN CHILDREN - Saparbaev , M.K; Yuldashev , A.A (Innovative Development in Educational Activities, 2023)
This review describes methods of treatment of odontogenic cysts of the jaw bones in children and surgical rehabilitation of patients with this pathology. Literary data on various methods of surgical treatment of odontogenic cysts of the jaw bones in children are summarized. The prospects for recognizing odontogenic cysts using computed tomography are noted; the decisive preference in making a diagnosis is given to mandatory patho-histological examination.